PKM Farmasipreneur Bagi Mahasiswa Sekolah Tinggi Farmasi Nusa Putera Semarang Tinggi Farmasi Nusa Putera Semarang - Maria Augustine Graciafernandy; Masine Slahanti; Scorina Dwiantari (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Entrepreneurship has become one of the subjects in universities including pharmaceutical colleges and colleges, but so far the motivation to become an entrepreneur has not been seen by many pharmacy students, because the tendency is that after they graduate from the academy they enter the world of work and work a lot in pharmacies. or familiarity. The purpose of this service is to motivate them to become pharmacists and develop according to the discipline they are pursuing. The dedication was carried out by holding a seminar attended by students of the Nusa Putera College of Pharmacy Semarang. The results of this activity became motivation and enthusiasm for students to understand the world of entrepreneurship in accordance with the education they are occupied so they can become pharmacistpreneurs